EFFECTIVENESS OF IMPLEMENTING ACADEMIC SUPERVISION IN IMPROVING TEACHER PERFORMANCE IN SMK NEGERI 5 PADANG - Emi Vovo Sembiring; Ikhsan Dani Nugraha (Jurnal Mantik, 2022)
Education has an important role in a nation. One of the functions of education is to build character in order to educate the nation's life. The realization of the value of education cannot be obtained instantly, it takes a long and sustainable time to obtain the value of education itself. One way to get educational values ??is at school. Through education in schools, every individual gains knowledge so that they have good thinking skills in solving problems and following the changing times that are increasingly sophisticated. The quality of education can increase because of the teachers. Professional and competent teachers will certainly provide good quality education. However, in reality, many teachers experience difficulties when teaching, such as the curriculum changing frequently, facilities and infrastructure are inadequate. Based on the description above, the researcher aims to see whether the supervision activities run well and optimally. The results of the teacher's work assessment in processing and developing a framework in order to achieve educational goals in schools. The approach in this study is a qualitative approach with descriptive methods through interviews, observation, and triangulation analysis. The results showed that academic supervision had a positive impact on the quality and quality of education. Especially for teachers who get coaching and training. Supervision activities are carried out in the following ways: observation before supervision activities, seeing firsthand the learning process, revising the results of supervision, and field supervision. An assessment is carried out to see how far the learning objectives have been achieved. Academic supervision activities can certainly improve the ability of teachers to be more professional.